Palliative Surgery for Rare Cases of Anterior Urethral Metastasis in Prostate Cancer - Enrique Gómez Gómez; Jose Carlos Carrasco Aznar; Maria del Mar Moreno Rodríguez; José Valero Rosa; Maria José Requena Tapia (Case Reports in Urology)
Penis metastasis from prostate cancer is very rare, and its management varies from case to case as there are very few cases reported in the literature. We describe a patient with prostate cancer treated with radiotherapy and androgen deprivation therapy who presented with urethral bleeding as a symptom of anterior urethral metastasis during followup. We propose a way to manage this and review the literature.